Intramuscular Corticosteroid Therapy in the Treatment of Alopecia Areata: A Time-to-Event Analysis - Chanprapaph K; Pomsoong C; Kositkuljorn C; Suchonwanit P (Dove Medical Press, 2022)
Kumutnart Chanprapaph, Cherrin Pomsoong, Chaninan Kositkuljorn, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat SuchonwanitDivision of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, ThailandTel +66-2-2011141Fax +66-2-201-1211 Ext 4Email poonkiat@hotmail.comIntroduction: Intramuscular corticosteroids (IMC) have gained popularity for the treatment of severe alopecia areata (AA) in recent years; however, evidence on their efficacy and safety is still limited.Objective: To evaluate the efficacy, relapse rate, and tolerability of IMC in the treatment of AA, as well as factors associated with treatment outcomes.Methods: Time-to-event analysis was performed on patients with severe, extensive, or rapidly progressive AA receiving IMC. The IMC regimen comprised triamcinolone acetonide 20- 40 mg/mL injected every 4- 6 weeks. The evaluated outcomes included initial (25% regrowth), significant (75% regrowth), and complete hair regrowth (100% regrowth). Relapse and adverse events were also noted. Factors associated with treatment outcomes and relapse were analyzed using the Cox proportional hazards model.Results: A total of 101 patients were eligible for analysis. Significant hair regrowth was obtained in 80.2% of the patients (n = 81), in a median time of 3.4 months (95% confidence interval [CI] = 2.9- 4.4). Complete hair regrowth was achieved in 48.5% of the subjects (n = 49), and relapse was observed in 47.5% (n = 48). Acneiform eruption was the most common adverse effect. Multivariable analysis revealed that nail involvement was a negative predictor of significant hair regrowth (adjusted hazard ratio [HR] = 0.04, 95% CI = 0.01- 0.55; P = 0.015), whereas duration of AA longer than 6 months was associated with disease recurrence (adjusted HR = 4.02, 95% CI = 1.52- 4.66; P = 0.005).Conclusion: This study demonstrated the efficacy and safety of IMC in the treatment of severe or active AA; however, the relapse rate remained relatively high after discontinuation of the therapy. Nail involvement was a negative predictor of significant hair regrowth, while disease duration longer than 6 months predicted AA relapse.Keywords: acute diffuse and total alopecia, alopecia totalis, alopecia universalis, hair loss, injection, systemic